Aspek Kriminologi Tindak Pidana Korupsi - Dewi Setyowati Dewi Setyowati; Sisca Muji Rahayu (Perspektif Hukum, 2021)
Corruption that is happening in Indonesia today, is already in a very serious position and is deeply rooted in every aspect of life. The development of corrupt practices from year to year is increasing, both in terms of quantity or amount of state financial losses as well as in terms of quality which are increasingly systematic, sophisticated and have expanded in scope in all aspects of society. Corruption is an act that can not only harm the state's finances but can also cause losses to the people's economy. This paper explores the criminological aspects of corruption. In the decision Number: 95/Pid.Sus-TPK/2019/PN. Sby stated that law enforcers from court institutions, namely the scope of the Registrar's Office, were involved in cases of criminal acts of abuse of authority which indicated a criminal act of corruption, namely bribery. The need for clear legal accountability for government officials in carrying out their duties and authorities is an essential requirement in an effort to realize law enforcement for criminal acts of corruption with legal certainty and justice.